2016
DOI: 10.2139/ssrn.2872050
|View full text |Cite
|
Sign up to set email alerts
|

Water Resources Management in Support of Raw Region Based on Decoupling Effect

Abstract: It determines the presence of the decoupling effect in the Russians raw regions materials by using water. Developed models that explain the relationship between the gross regional product and water intake. It proved no effect on the growth of water consumption in most regions of the reference commodity. Recommendations for the decoupling effect development in support of Russians raw regions. Content from this work may be used under the terms of the Creative Commons Attribution 3.0 licence. Any further distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Dasgupta et al [27] analyzed the Indian energy intensity trends from 1973 to 2012 and concluded that the decline in energy intensity could offset a major portion of the growing energy demand, leading to a decoupling trend. Lesin et al [28] utilized Russian water use to determine the decoupling effect of raw material.…”
Section: Research At the National Or Provincial Levelmentioning
confidence: 99%
“…Dasgupta et al [27] analyzed the Indian energy intensity trends from 1973 to 2012 and concluded that the decline in energy intensity could offset a major portion of the growing energy demand, leading to a decoupling trend. Lesin et al [28] utilized Russian water use to determine the decoupling effect of raw material.…”
Section: Research At the National Or Provincial Levelmentioning
confidence: 99%
“…In the field of water consumption decoupling, Lesin et al (2016) obtained the decoupling relationship between economic growth and water consumption by discussing the reasons why water pollution supports the weak regional economic growth. Wang (2015) applied decoupling theory and Tapio elasticity analysis to analyze the relationship between China's economic growth and water resource utilisation from the perspective of time and space and concluded that the decoupling between industrial production and industrial water use was weaker than that in agriculture.…”
Section: Literaturementioning
confidence: 99%
“…By discussing the decoupling practice between economic development and resource consumption, Zhou et al (2014) put forward policy suggestions focusing on the real economy for China to achieve sustainable and stable economic growth. Similarly, on the basis of decoupling theory, Lesin et al (2017) innovated the management method of water resources in Russia.…”
Section: Literaturementioning
confidence: 99%